INTEGRASI KOMUNIKATIF PENDIDIKAN ISLAM MUHAMMAD IQBAL DAN HAMKA - AIDA ZUBAIDAH (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2018)
This research is a library research which examines the source of the data in the form of literature that related to the research problem. This research used qualitative approach. The data was obtained by analyzing the source of the data, so that the researcher used descriptive analysis method. Muhammad Iqbal in his taught in education suggests that education should be Islamic and dynamic, creative, and aimed to foster and give the opportunity to the spirit of creativity in every human being, besides to arm with the ability to master art, and new knowledge, intelligence and strength. However, Hamka suggest that education process is not only oriented on the material factors. That approach could not bring human being to the spiritual satisfaction. The form of harmony and integral education is the characteristic of ideal and effective Islamic education in order to obtain what we want, that is produced students that have good personality (insane kamil)